2017
DOI: 10.17802/2306-1278-2017-1-92-101
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Mutagenesis in Atherosclerosis

Abstract: Федеральное государственное бюджетное научное учреждение «Научно-исследовательский институт комплексных проблем сердечно-сосудистых заболеваний»,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 67 publications
(56 reference statements)
0
3
0
1
Order By: Relevance
“…В настоящее время создание комплексных моделей прогнозирования отдаленных исходов становится акту-ОРИГИНАЛЬНЫЕ СТАТЬИ § альной задачей, а учет генетических факторов риска расширяет возможности прогнозирования риска и влияет на выбор лечебной стратегии [21]. В 2017 г. была опубликована математическая модель прогнозирования риска развития НКС в течение года после ОКСбпSТ, включающая, помимо клинических факторов риска, такие факторы, как концентрация С-реактивного протеина в сыворотке крови и носительство генотипа С / Т rs1376251 гена TAS2R50, что позволяет повысить ее прогностическую ценность [22].…”
Section: Discussionunclassified
“…В настоящее время создание комплексных моделей прогнозирования отдаленных исходов становится акту-ОРИГИНАЛЬНЫЕ СТАТЬИ § альной задачей, а учет генетических факторов риска расширяет возможности прогнозирования риска и влияет на выбор лечебной стратегии [21]. В 2017 г. была опубликована математическая модель прогнозирования риска развития НКС в течение года после ОКСбпSТ, включающая, помимо клинических факторов риска, такие факторы, как концентрация С-реактивного протеина в сыворотке крови и носительство генотипа С / Т rs1376251 гена TAS2R50, что позволяет повысить ее прогностическую ценность [22].…”
Section: Discussionunclassified
“…Genotoxic stress in mammalian cells is defined as a situation that initiates DNA damage compromising the cell's genomic integrity leading to replication and transcription arrest [1] and underlies many pathological conditions including cellular senescence [2][3][4][5], cancer [6][7][8][9] and cardiovascular diseases [10][11][12][13][14]. Recent experimental data suggest that the genotoxic stress in vitro induced by alkylating mutagen mitomycin C (MMC) is associated with the proinflammatory activation of primary human endothelial cells and the endothelial-to-mesenchymal transition [15][16][17], the key pathways underlying endothelial disfunction [18]-an initial stage of atherosclerosis [19,20], a leading cause of cardiovascular morbidity and mortality worldwide [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was reported that genotoxic stress induced by 6 h of exposure of endothelial cells to 500 ng/mL MMC is associated with proinflammatory activation of endothelium and endothelial dysfunction [ 17 , 18 , 19 ] underlying atherosclerosis [ 20 , 21 ], a leading cause of cardiovascular morbidity and mortality worldwide [ 22 , 23 ]. HMG-CoA (3-hydroxy-3-methylglutaryl-coenzyme A) reductase inhibitors, also known as statins, are small molecules that are the rate-controlling enzyme of the mevalonate pathway.…”
Section: Introductionmentioning
confidence: 99%